A Debt Overhang Model for Low-Income Countries : Implications for Debt Relief - Koeda, Junko (Washington, D.C. : International Monetary Fund, 2006)
The paper presents a theoretical model to explain how debt overhang is generated in low-income countries and discusses its implications for debt relief. The paper indicates that the extent of debt overhang, and the effectiveness of debt relief, would depend on a recipient country's initial economic conditions and level of total factor productivity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet